2011
DOI: 10.1093/nar/gkr380
|View full text |Cite|
|
Sign up to set email alerts
|

A protein shuttle system to target RNA into mitochondria

Abstract: Mitochondria play a key role in essential cellular functions. A deeper understanding of mitochondrial molecular processes is hampered by the difficulty of incorporating foreign nucleic acids into organelles. Mitochondria of most eukaryotic species import cytosolic tRNAs. Based on this natural process, we describe here a powerful shuttle system to internalize several types of RNAs into isolated mitochondria. We demonstrate that this tool is useful to investigate tRNA processing or mRNA editing in plant mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…This assay involves the import of radiolabeled tRNA for Ala (tRNA Ala ), a well-characterized nucleus-encoded tRNA shown to be imported in vivo into plant mitochondria (Small et al, 1992). tRNA import assays are carried out with the addition of a carrier protein, Su9-DHFR (the presequence of subunit 9 of mitochondrial ATP synthase from Neurospora crassa linked to dihydrofolate reductase), that has been shown to allow for the efficient uptake of tRNA Ala in isolated mitochondria (Sieber et al, 2011). It was observed that the uptake of radiolabeled tRNA Ala into mitochondria isolated from tric1tric2 was reduced significantly by approximately 80% compared with mitochondria from wild-type (Col-0) plants (Fig.…”
Section: Tric1 and Tric2 Interact With Components Of The Tom And Tim mentioning
confidence: 99%
See 1 more Smart Citation
“…This assay involves the import of radiolabeled tRNA for Ala (tRNA Ala ), a well-characterized nucleus-encoded tRNA shown to be imported in vivo into plant mitochondria (Small et al, 1992). tRNA import assays are carried out with the addition of a carrier protein, Su9-DHFR (the presequence of subunit 9 of mitochondrial ATP synthase from Neurospora crassa linked to dihydrofolate reductase), that has been shown to allow for the efficient uptake of tRNA Ala in isolated mitochondria (Sieber et al, 2011). It was observed that the uptake of radiolabeled tRNA Ala into mitochondria isolated from tric1tric2 was reduced significantly by approximately 80% compared with mitochondria from wild-type (Col-0) plants (Fig.…”
Section: Tric1 and Tric2 Interact With Components Of The Tom And Tim mentioning
confidence: 99%
“…The uptake of tRNA was first shown in vivo in plant mitochondria in 1992 (Small et al, 1992). Subsequently, an in vitro tRNA uptake assay was established, which showed the uptake of cytosolic tRNA into isolated mitochondria (Sieber et al, 2011). Further studies have suggested that there is cooperation among components of the protein import translocase of the outer membrane (TOM) and Porin/voltage-dependent anion channel (VDAC), although specific proteins dedicated for the import of tRNA have yet to be identified (Salinas et al, 2006).…”
mentioning
confidence: 99%
“…The general importance of VDAC in plant has only recently emerged. VDAC might be the important component of the tRNA import machinery in plant mitochondria [1416]. Besides their role in metabolite transport, plant VDACs are also involved in programmed cell death [17].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a further strategy for the introduction of nucleic acids into mitochondria was described by Sieber et al (2011) who used an RNA-binding protein as a vehicle to import RNAs up to 800 nt in size into isolated mitochondria. It was shown that the mammalian dihydrofolate reductase (DHFR), fused to a mitochondrial-targeting sequence (MTS), is able to bind RNAs in a nonspecific manner.…”
Section: Carrier Protein-driven Rna Importmentioning
confidence: 99%
“…Upon import, a tRNA precursor was correctly processed, leading to a mature tRNA. Similarly, after DHFR-driven uptake, the unedited version of the potato mitochondrial atp9 messenger RNA (mRNA) was partially edited in organello (Sieber et al 2011). …”
Section: Carrier Protein-driven Rna Importmentioning
confidence: 99%